ANALISIS KEPUASAN PELANGGAN MCDONALDS TEBET JAKARTA SELATAN - Bimo Figo Andito, (2022)
This study is a quantitative study and aims to determine the effect of service quality, product quality, and discounts on customer satisfaction at McDonald's Tebet, South Jakarta. The population in this study were McDonald's Tebet South Jakarta customers with the criteria of having bought 2 or more times. Sampling using non-probability sampling method with purposive sampling technique, with a total sample of 100 respondents. The data analysis technique was carried out by descriptive and inferential analysis using Partial Least Square (PLS) tools. The results of this study indicate that the service quality variable has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction, and discounts have a positive and significant effect on customer satisfaction. The result of the calculation of the determinant coefficient is 0.720. This shows that service quality, product quality, and discounts affect customer satisfaction at McDonald's Tebet, South Jakarta by 72% and the remaining 28% is influenced by other variables.